Fostering Trauma-Informed and Eudaimonic Pedagogy in Music Education - Walzer, Daniel (Frontiers in Education, 2021)
The arts and entertainment sectors remain fragile because of the global pandemic. Unemployment, physical and emotional stress, social isolation, a loss of purpose, and a problematic future are just a sample of the ongoing traumas that music educators and practitioners experience under duress. As an inherently social activity, music-making becomes especially difficult when the threat of infection persists, further exacerbating somatic trauma and decreased health and wellness. The sudden loss of daily contact with others, coupled with multiple kinds of crises, complicates matters for educators. How does one flourish when their livelihood, personal connections, and sense of meaning-making disappear? Likewise, how ought the music educator navigate such uncertainty when teaching others? To address these issues, psychologists have often turned to Trauma-Informed Care (TIC), a collaborative model between the practitioner and client that recognizes and validates the impact of painful memories and experiences. This article advocates for a compassionate eudaimonic pedagogy model that prioritizes healing and self-care for teachers and students and cultivating an ethos of critical digital pedagogy—itself a form of eudaimonia. Drawing on Noddings’ (1992, 1995, 2002) Philosophy of Care, the article concludes with suggestions on future connections between eudaimonia and music education.